Understanding The Role Of Civics Education Teachers In Shaping Children's Social Character At SMPN 3 Bilah Hulu School - Sapriani, Bella; Anjar, Agus; Junita (EduLine: Journal of Education and Learning Innovation, 2024)
The background of this research, there are some students who do not foster a social spirit in their environment. The purpose of the research is to find out how the Civics teaching staff in fostering social character in students. Then the method used by doing a qualitative descriptive approach. This qualitative descriptive researcher uses by observing the problems that researchers raise, the findings will later be narrated in the form of words to get a conclusion on the problems that researchers raise. To make it easier for researchers, the instrument used is an open interview in order to explore information from Civics teachers about fostering the spirit of social character in students in depth. The results of the discussion that teachers have a big role in shaping the social character of their students, especially Civics Education teaching staff because it is required that students can practice what has been stated in the values of Pancasila. The big impact of the success of the Civics Education teacher is to give birth to a generation with a religious spirit, honesty, discipline, responsibility, care, tolerance, mutual cooperation, courtesy, self-confidence.